Correction: Achieving a low-carbon future through the energy–chemical nexus in China. Issue 18 (18th August 2021) - Li, Yinan; Lan, Song; Pérez-Ramírez, Javier; Wang, Xiaonan
Abstract : Correction for 'Achieving a low-carbon future through the energy–chemical nexus in China' by Yinan Li et al., Sustainable Energy Fuels, 2020, 4, 6141–6155, DOI: ; 10.1039/D0SE01337D .